Artificial Skin: Microstructured Graphene Arrays for Highly Sensitive Flexible Tactile Sensors (Small 18/2014). Issue 18 (September 2014) - Zhu, Bowen; Niu, Zhiqiang; Wang, Hong; Leow, Wan Ru; Wang, Hua; Li, Yuangang; Zheng, Liyan; Wei, Jun; Huo, Fengwei; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> Flexible tactile sensors with outstanding sensitivity in the low pressure regime are in demand for the development of artificial skin. On page 3625, X. Chen and co‐workers devise a resistive tactile sensor using microstructured graphene arrays as sensitive layers. The introduction of the anisotropic microstructure arrays makes the sensor sensitive and fast to external pressure. It also shows a remarkable capability in information transmission, demonstrating great potential for application in human‐machine interfaces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>